Scientific articles in engineering: Constituent and distinctive elements of the genre - Arauz , Valéria Angélica Ribeiro (Seven Editora, 2024)
This research originated from the need to better understand the structure and composition of the scientific article genre, with an emphasis on the field of Engineering I. The objective was to analyze this genre in terms of its textual and discursive characteristics to aid researchers and students in writing their own articles. An exploratory and descriptive research was conducted, employing a methodology based on the rhetorical moves outlined in John Swales’ (1990) CARS (Creating a Research Space) model, with further developments studied by Swales (1981; 1990; 2009), Motta-Roth and Hendges (1996; 1998), Santos (1995), and Berdanier (2019). The genre elements analyzed in detail included the discourse community, the statement of the research problem, the abstract, the introduction, and the methodology section. As a result, a mapping of the rhetorical moves and the main syntactic-semantic structures involved in each of the sections studied was created, based on their recurrence in 50 articles published in prominent journals in the fields of civil engineering, environmental and sanitary engineering, and transportation engineering. DOI:https://doi.org/10.56238/sevened2024.009-032